Identification of Subsurface Rock Structure of Non-Volcanic Geothermal Systems Based on Gravity Anomalies (Terak Village, Central Bangka Regency) - Reza Firdaus; Siska Oktaviyani; Putri Hardianti; Anisa Indriawati; Tri Kusmita (Politeknik Negeri Batam, 2021)
Abstract Geothermal manifestations on Bangka Island are found in the villages of Terak, Pemali, Sungailiat/Pelawan, Dendang, Permis, and Nyelanding. The manifestation of hot water in Terak Village, Central Bangka Regency is in the form of 3 hot springs with a surface temperature of 55ᵒC this research is to be carried focus on the structure of the subsurface rock layers using the geophysical method, namely the gravity method. The data used are topography and Free Air Anomaly. The data processing is in the form of Bouguer Correction and Terrain Correction to obtain the Complete Bouguer Anomaly (CBA) value. Then the CBA value is separated from regional anomalies and residual anomalies using the upward continuation method, as well as 2D modeling interpretation (forward modeling). From the research results, it is known that the subsurface rock structure of the non-volcanic geothermal system in Terak Village in the form of sandstone (2.28 – 2.49 gr/cm3) at a depth of 0 – 1.44 km is estimated as caprock, granite (2.77 – 2.78 gr/cm3) at a depth of 0 – 1.8 km is estimated as reservoir rock, and diorite rock (2.87 – 2.99 gr/ cm3) at a depth of 0 – 2 km is estimated as basement rock.